Cross Cultural Differences Leisure Behavior: The Armenian Community - BAŞKAN, Aytekin Hamdi; KARAKÜÇÜK, Suat (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2015)
In this study, the changing world order, leisure time, are organized according to particular norms of capitalist values and includes a new meaning and usage. The theoretical approach to leisure time, free time carries the ideological, political, and social changes that highlight the capitalist. Leisure and variable devices on the dominant role and the nature of the subject of criticism has been particularly susceptible to commercial exploitation in modern societies, and highlights the approaches mentioned before, and idle time approaches, with emphasis on cultural buildings with the modern era has acquired free time brought a new openness to views of Armenian Culture will be examined with reference to the element of ethnic origin. We talked with 32 Armenian people who live in Vakifli village of Hatay-Samandag. We search their leisure time activities about their culture. Armenian people who live in provincial, generally do church originated activities, hunting, doing some fests, meetings and dances. These people, who are particularly isolated from groups and general, are usually do activities like watching television, or going to cafes.